Abrasion and chemical resistance of composite vitreous enamel coatings with hard particles. (26th November 2015) - Rossi, S.; Fedel, M.; Deflorian, F.; Parziani, N.
Abstract : Vitreous enamels are coatings commonly used to protect aluminium substrates, because of their very good protection properties together with aesthetical ones. The properties of this layer can be optimized changing the chemical composition of the starting frit or with mill additives. The addition of hard particles, very common method with other types of coatings, for this layer has not yet been studied. The aim of this research is to study how the addition of hard particles influences the mechanical and chemical resistance of enamels applied on AA4006 alloy. Deposits with two different kinds of particles [tungsten carbide (WC) and silicon carbide (SiC)] with two concentrations were considered. The enamel layer without particles was considered as reference. Two different kinds of abrasion test (Taber and PEI) were adopted to study the abrasion resistance. Enamel coatings' properties were characterized considering the changes in mass, gloss and roughness values before and during abrasion tests. Moreover, the observation of cross sections and surfaces permitted to evaluate the coatings' quality and to obtain information about the damage mechanisms. The most improved abrasion resistance was achieved using the concentration of 10 vol% for SiC and 5 vol% for WC. Therefore, the adding of hard particles could be a valid solution to improve the abrasion resistance of the vitreous enamels. The chemical resistance behaviour was checked with immersion into acid and basic solutions. The presence in the layer of SiC particles produced a reduction of resistance in presence of acidic solution, while enamel with WC particles resulted more resistant. Copyright © 2015 John Wiley & Sons, Ltd.